Cognitive therapy versus exposure and applied relaxation in social phobia: A randomized controlled trial. - Clark, D; Ehlers, A; Hackmann, A; McManus, F; Fennell, M; Grey, N; Waddington, L; Wild, J (2006)
A new cognitive therapy (CT) program was compared with an established behavioral treatment. Sixty-two patients meeting Diagnostic and Statistical Manual of Mental Disorders (4th ed.; American Psychiatric Association, 1994) criteria for social phobia were randomly assigned to CT, exposure plus applied relaxation (EXP = AR), or wait-list (WAIT). CT and EXP = AR were superior to WAIT on all measures. On measures of social phobia, CT led to greater improvement than did EXP = AR. Percentages of patients who no longer met diagnostic criteria for social phobia at posttreatment-wait were as follows: 84% in CT, 42% in EXP = AR, and 0% in WAIT. At the 1-year follow-up, differences in outcome persisted. In addition, patients in EXP = AR were more likely to have sought additional treatment. Therapist effects were small and nonsignificant. CT appears to be superior to EXP = AR in the treatment of social phobia.